Analisis Finansial Usaha Hidroponik (Studi Kasus: Gumineponik di Denpasar Timur Kota Denpasar Provinsi Bali) - I Nyoman Tantra Pradnyana; I Ketut Suamba; Ni Wayan Sri Sutari (Nandur, 2021)
Land conversion in urban areas causes various kinds of problems. One of them is agriculture. This thing requires innovation and contribution of the millennial generation to develop urban agriculture (Urban Farming), especially hydroponics. There is one of the businesses engaged in the hydroponic sector in Denpasar Bali namely Gumineponik. This business engaged in agriculture especially hydroponics and culinary. It is located in East Denpasar, Denpasar City, Bali Province. The background of this business was established because of the large number of land conversions that occurred in Denpasar City, especially in East Denpasar District that resulted in reduced agricultural land. This business is a solution in the midst of the problem of land conversion by utilizing narrow land to be more productive with hydroponic cultivation. Gumineponik is a business that has an upstream to downstream concept starting from the vegetables production process, hydroponic equipment, and post-harvest processing. It introduces the millennial generation about modern agriculture that does not require large land so that it can be efficient and effective in terms of productivity of agricultural products. Utilizing social media through online marketing such as Instagram, Facebook, and Whatsapp are used to make this business reaches wider market effectively. This research uses descriptive qualitative and quantitative method. Qualitative descriptive analysis is used to describe the system, concept and output of Gumineponik based on technical, economic and social aspects. Quantitative analysis is used to measure financial feasibility on the economic aspect through approaches (profit and loss statements, balance sheets, financial projections for 3 years and Net B/C Ratio). The results of the financial analysis of Gumineponik are a healthy business with an average profit value of Rp. 6,811,667 in a month during 2020, with an average profit margin of 28% and a Net B/C Ratio of 1.33. These results indicate that Gumineponik has healthy finances and relatively growing.